Guidelines for Preparation of the Seafood Industry move towards migrant workers returning to the country. Case Study: Samut Sakhon Province. - sukcharoen, Bantita; Sangaramrungloj, Woraphot; Kam-On, Praison (วารสารวิจัยราชภัฏธนบุรี รับใช้สังคม, 2025)
Abstract This research aimed to recommend policy, planning, logistic and supply chain readiness and human resource management of the seafood industry moving towards migrant workers return to the country. It was mixed with both qualitative and quantitative research. The sample group consisted of 165 entrepreneurs and 8 experts. Sample collection, random sampling, and instruments depending upon each of the research stages were assigned appropriately Statistical analysis tools in this research were percentage, mean, standard deviation stepwise multiple regression analysis (MRA). The research results were: 1) The guidelines for the preparation of the seafood industry moving towards migrant workers return to the country has four approaches: organizational Planning, adhering to Provincial Policies, worker Planning, adopting Modern Technology as THAILAND 5.0 Policy and agriculture for export 2) Entrepreneurs potentiality of logistics and supply chain and human resource management for the seafood industry of Samut Sakhon, the potential strategic of government support and development of the central lower region Samut sakorn province, potential competing models moving towards migrant workers return to the country. Developing potentiality of seafood industry entrepreneurs at Samut Sakhon. Overall, the high level (= 4.29, SD = 0.54, = 4.31, SD = 0.59, = 4.28, SD = 0.72, = 3.64, SD = 0.73, respectively, 3) potential entrepreneurs 3 sides affecting the new Labor market, expansion of trade, cost, and revenue of the entrepreneurs’ variation was 30.5%, 18.5%, 11.70%, 4%, respectively Keywords: Migrant Workers; Seafood Industry; logistics, Supply Chain, Human Resource management